COMPETITIVE ABILITY OF CANOLA HYBRIDS WITH WEEDS - GALON,L. (2015)
ABSTRACTThe objective of the study was to assess the relative competitive ability of canola hybrids in the presence of turnip (Raphanus sativus) and ryegrass (Lolium multiflorum) in different ratios of plants in the mixture. The experiments were conducted in a greenhouse, in a completely randomized design with four replications. Treatments were arranged in ratios of canola against turnip or ryegrass: 100:0, 75:25, 50:50, 25:75 and 0:100. Competitive analysis of the species was accomplished by means of diagrams usually applied to replacement series and also by the relative competitiveness indices. Fifty days after the emergence of the species, measurements of leaf area and shoot dry mass were performed. There was a competition between canola hybrids and weeds, with reduction for all variables. There was a differential competitive ability among canola hybrids in the presence of turnip and/or ryegrass. Canola hybrid Hyola 433 was more competitive in the presence of turnip than Hyola 61, 76 and 571 CL. Hyola 61, 76, 433 and 571 CL do not differ in terms of competition ability when growing with ryegrass.